Analysis and Verification of Algeria KAE 3MWp Solar Power Plant Electrical Capacity Calculation Report. (October 2020) - Ye, Xiang
Abstract: The electrical capacity calculation report of Algeria KAE 3MWp Solar Power Plant is specifically analysized and verified. The analysis results show that the EPC contractual and conceptional design is applicable and further optimization works is possible to be implemented during construction design stage, the technical requirements for both electricity production and PR values are confirmed within efficient ranges.